PEMBARUAN KONTROL SISTEM INDONESIA LOW SPEED TUNNEL - Parulian, Franky Surya (-)
AbstractIndonesian Low-Speed Tunnel (ILST) has been in operation since February 1987, whose operation is supported by 10 units of the ILST-facility plant, each ILST-facility plant works according to its duties and can be operated locally (onsite) and remotely (from control room/control desk). Local and remote Operations are made possible by system control?s installation at each ILST-facility plant. The control systems used are the Programmable Logic Controller (PLC), which is installed at each -ILST facility plant as local PLC and central PLC.For remote operations, a communication module is installed at local and central PLC. The PLC used by ILST was SATTControl running CPM operating system which is not commonly used anymore, and the spare parts are difficult to find because the PLC manufacturers have confirmed that they no longer provide technical support or spare parts since 2001.To ensure ILST?s continues operations, ILST?s control system update is carried out. The updates include old PLC checks, new locally available PLC surveys, compatibility with existing PLCs, windows-based hardware and software flexibility, inter PLCs communication, system?s reliability and suited with yearly available budget.Keywords: ILST system control, PLCAbstrakIndonesian Low Speed Tunnel (ILST) telah beroperasi sejak Pebruari 1987, dimana dalam operasinya didukung oleh 10 unit plant fasilitas-ILST, dimana plant fasilitas-ILST bekerja sesuai tugas plant masing-masing dan dapat dioperasikan secara local control (onsite) dan secara remote dari ruang kontrol (desk control). Pengoperasian secara local dan remote tersebut dimungkinkan dengan pemasangan kontrol sistem pada masing-masing plant fasilitas-ILST, kontrol sistem yang digunakan adalah Programmable Logic Controller (PLC), yang dipasang di tiap plant fasilitas-ILST sebagai local PLC dan central PLC.Untuk operasi remote dimana dipasang module komunikasi pada local dan central PLC. PLC yang digunakan ILST adalah SATTControl yang menggunakan operating system CPM yang tak umum lagi digunakan saat ini dan sulit mencari spare part karena produsen PLC telah mengkonfirmasi bahwa tak ada lagi dukungan teknis dan spare parts sejak tahun 2001.Untuk kelangsungan operasi ILST dilakukan pembaruan kontrol sistem ILST, pembaruan meliputi pemeriksaan PLC lama, survey PLC baru di dalam negeri, kecocokan dengan PLC existing, flexibilitas hardware dan software yang berbasis windows, komunikasi antar PLC, kehandalannya dan sesuai dengan dana yang diperoleh tiap tahun.Kata kunci: control system ILST, PLC